Stratifying empiric risk of schizophrenia among first degree relatives using multiple predictors in two independent Indian samples - Bhatia, Triptish (Asian J Psychiatr, 2016)
BACKGROUND: Schizophrenia (SZ) has an estimated heritability of 64–88%, with the higher values based on twin studies. Conventionally, family history of psychosis is the best individual-level predictor of risk, but reliable risk estimates are unavailable for Indian populations. Genetic, environmental, and epigenetic factors are equally important and should be considered when predicting risk in ‘at risk’ individuals. OBJECTIVE: To estimate risk based on an Indian schizophrenia participant’s family history combined with selected demographic factors. METHODS: To incorporate variables in addition to family history, and to stratify risk, we constructed a regression equation that included demographic variables in addition to family history. The equation was tested in two independent Indian samples: (i) an initial sample of SZ participants (N = 128) with one sibling or offspring; (ii) a second, independent sample consisting of multiply affected families (N = 138 families, with two or more sibs/offspring affected with SZ). RESULTS: The overall estimated risk was 4.31 ± 0.27 (mean standard deviation). There were 19 (14.8%) individuals in the high risk group, 75 (58.6%) in the moderate risk and 34 (26.6%) in the above average risk (in Sample A). In the validation sample, risks were distributed as: high (45%), moderate (38%) and above average (17%). Consistent risk estimates were obtained from both samples using the regression equation. CONCLUSIONS: Familial risk can be combined with demographic factors to estimate risk for SZ in India. If replicated, the proposed stratification of risk may be easier and more realistic for family members.